Effectiveness of Super-plasticizer on High Volume Fly Ash Concrete - Tay, Lee Peng (Universiti Teknologi PETRONAS, 2006)
This research project was aimed to determine the optimum super-plasticizer dosage for producing highly workable, high strength, low porosity and low gas permeability concrete containing high volume fly ash ( 60%) as partial cement replacement. The trial mix with 100% cement was initiated with a water cement ratio of 0.27, which gave very dry mix with negligible slump value. The mix resulted quite poor quality hardened concrete cubes. Then on the next trial, the mix was also not very successful. Finally a mix with 0.4 water cement ratio yielded targeted results and chosen as the final mix water ratio. Super-plasticizer dosage of 0%, 0.5%, I%, 1.5%, 2%, 2.5% and 3% were tested. It is found that super-plasticizer dosage in the range of 1.5% to 2.5% has given the optimum characteristics of concrete including strength, porosity and the gas permeability up to 90 days and 1.5% yields the optimum dosage of super-plasticizer.